Cyberculture as a component of professional training of mathematics and informatics teachers - Chobo Hei; Stoika Myroslav; Sztojka Miroszláv; Стойка Мирослав (II. Rákóczi Ferenc Kárpátaljai Magyar Egyetem, 2025)
Abstract. Problem Statement. Bullying and cyberbullying are widespread phenomena in contemporary educational environments, negatively affecting the development of children and adolescents. The problem has persisted even during the war: in 2023, 96 cases of bullying were registered in Ukraine, with a total of 614 cases over the past five years. Cyberbullying poses particular danger due to the widespread use of digital technologies, as children and adolescents make up one-third of global internet users. International studies indicate increasing online victimization, while traditional bullying is decreasing. This underscores the need to develop effective pedagogical strategies for preventing bullying and fostering safe digital behavior among participants in the educational process. Analysis of Current Research. The issue of cyberbullying and its prevention is actively studied by both international and Ukrainian scholars. International researchers, including K. Barrett, R. Kowalski, S. Limber, P. Smith, J. Finkel, and J. Yunoven, investigate factors contributing to cyberbullying, role structures, and behavioral characteristics of participants in digital harassment. Ukrainian scholars, such as H. Yefremova, Z. Zalibovska, O. Motlyakh, T. Tsyuman, K. Chaban, and B. Petrenko, analyze the psychological and pedagogical aspects of cyberbullying, its consequences for educational participants, and the role of digital technologies in the spread of aggression. Main Content. The internet has become an integral part of modern life, providing broad opportunities for communication, information search, learning, and various activities through social networks, online courses, video lessons, virtual libraries, and educational projects (Біда, Кучай, Сироєжко, 2023). At the same time, digitalization introduces new threats, with cyberbullying being particularly dangerous – deliberate, repeated actions using digital technologies to humiliate, intimidate, or psychologically pressure victims. Cyberbullying is characterized by perpetrator anonymity, rapid information dissemination, and prolonged psychological impact. A safe educational environment requires not only material and technical protection but also psychological and informational security, development of information culture, legal competence, and skills for safe communication (Мафтин, 2024).
Teljes kiadvány: https://kme.org.ua/uk/publications/rol-bezpeki-v-transkordonnomu-ta-mizhnarodnomu-spivrobitnictvi/
Keywords: cyberbullying; mathematics and informatics teachers; education